Strategi Komunikasi Kementerian Agama Kota Bengkulu Mencegah Stunting melalui Bimbingan Perkawinan Kepada Calon Pengantin - Ariza Diansari, Ariza Diansari; Dhanurseto Hadiprashada, Dhanurseto Hadiprashada; Neneng Cucu Marlina, Neneng Cucu Marlina (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The Government of the Republic of Indonesia through Presidential Regulation Number 72 of 2021 has designated prospective brides (catin) as one of the targets for accelerating stunting reduction from the upstream sector in order to achieve a quality generation of the nation. One of the roles carried out by the Ministry of Religion of the Republic of Indonesia is by preventing stunting through marriage guidance to prospective brides and grooms (Bimwin Catin). As a vertical agency at the Regency/City level, the Bengkulu City Ministry of Religion also provides marriage guidance to prospective brides and grooms (Bimwin Catin). The aim of this research is to find out the communication strategies used by the Bengkulu City Ministry of Religion to prevent stunting through marriage guidance to prospective brides and grooms in 2022. The research uses a qualitative approach through case studies. Data collection techniques used were observation, in-depth interviews and documentation. Researchers used communication strategy steps from Hafied Cangara (2014), consisting of selecting and determining communicators, setting targets and analyzing audience needs, techniques for composing messages, choosing media/communication channels, and analyzing communication effects. The results of this research are (1) The Bengkulu City Ministry of Religion prioritizes State Civil Apparatus (ASN) who have a Bimwin facilitator certificate as communicators, (2) Prospective brides and grooms are the target audience with a need for an audience of 500 people in 2022, (3) The City Ministry of Religion Bengkulu uses persuasive techniques in compiling and conveying messages to the prospective bride and groom, (4) the Ministry of Religion of Bengkulu City chooses public communication channels in the form of socialization in holding Bimwin Catin, (5) the Ministry of Religion of Bengkulu City receives a positive response where the prospective bride and groom experience a change in attitude after receiving information related to stunting